Physico-Chemical, and Sensory Properties of Soy Based Gouda Cheese Analog Made from Different Concentration of Fat, Sodium Citrate and Various Cheese Starter Cultures - Amar, Abu; Surono, Ingrid Suryanti (Makara Journal of Technology, 2012)
Gouda cheese analog (GCA) was made using soy protein isolate (SPI), skim milk powder (SMP), fat (palm fat and butter fat), and water (W) at optimal ratio of SPI : SMP : F : W = 14 : 6 : 20 : 60. The effects of butter fat, sodium citrate, and cheese starter culture on the sensory properties of ripened product were assessed by preference test, hedonic test, and the texture profile analysis (TPA) of GCA. The free fatty acids, water-soluble nitrogen, and reduction in pH value of progel were also measured. The use of 100% butter fat (BF) produced strong Gouda flavor. It could be due to the fatty acids content in BF; in contrast, product with 100% palm fat (PF) produced tasteless GCA. It might be due to fatty acids content in PF, middle, and long chain fatty acids. Single cheese starter culture could not develop Gouda flavor during ripening. The use of mixed fat (50% BF and 50% PF) and mixed cheese starter culture together with Brevibacterium linens developed a suitable characteristic flavor of Gouda product during ripening. The addition of 0.5% sodium citrate could improve the flavor; nevertheless, it reduced the stability of texture.